A Critique on the Book Economic Evaluation of Projects (Advanced subjects) - Fatemeh Mehrabani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Engineering economics is one of the branches of economics. It is effective in implementing the goal of the economy, which is the optimal allocation of resources to unlimited human demands. One of the published books in the field of optimal allocation, planning, and policy-making is "Economic Evaluation of Projects". The purpose of writing such a book is to teach the concepts needed by economic activists and their application in making the right decisions in order to prevent the waste of economic resources. The present book, due to various shortcomings such as lack of innovation, presentation of concepts in a scattered and out of order way and lack of a practical example that comprehensively covers the subject, lack of proper formulation of topics related to the advanced concept deals more with practical topics than advanced topics - and the inclusion of some general topics that have no place in advanced and specialized topics, failure to present the behavioral goals of each chapter, inconsistency of title and content from achieving explanation, description and proper description of the subject and purpose are other drawbacks of the present book. The book mentioned in this article has been reviewed in a critical-argumentative way, in the field of library studies, away from any prejudices and with fairness, and some parts have been researched and elaborated.